H. pylori Eradication Treatment Causes Alterations in the Gut Microbiota and Blood Lipid Levels - Martín-Núñez, Gracia M.; Cornejo-Pareja, Isabel; Roca-Rodríguez, M. del Mar; Clemente-Postigo, Mercedes; Cardona, Fernando; Fernández-García, José C.; Moreno-Indias, Isabel; Tinahones, Francisco J. (Frontiers in Medicine, 2020)
Background: The gut microbiome plays an important role in the lipid metabolism. Antibiotic treatment causes changes in the intestinal microbiota. Our objective was to explore the relationship between changes in the intestinal microbiota and the level of plasma high density lipoprotein cholesterol (HDL) and low density lipoprotein cholesterol (LDL). Methods: Prospective case-control study with Helicobacter pylori-positive patients undergoing eradication therapy with omeprazole, clarithromycin, and amoxicillin. Stool and blood samples were obtained from 20 controls (H. pylori negative) and 40 patients before and 2 months after antibiotic treatment. Gut microbiota was determined through 16S rRNA amplicon sequencing (Illumina MiSeq). Results: Eradication treatment for H. pylori increased the HDL levels, and caused changes in gut microbiota profiles. An unfavorable lipid profiles (high LDL and low HDL levels) was associated with a low microbial richness and an increase of the Bacteroidetes phylum. Prevotella copri, Lachonobacterium, and Delsufovibrio were positively associated with HDL while Rikenellaceae was negatively associated with HDL after completing antibiotic treatment. Conclusions:Helicobacter pylori eradication treatment could improve lipid metabolism in relation with an increase in the HDL. Changes in the abundance of specific bacteria, such as P. copri, Lachonobacterium, Delsufovibrio, and Rikenellaceae could be associated with change in the plasma HDL levels.